2018
DOI: 10.3892/ol.2018.9415
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between CT signs and the expression of miR‑146a in colon cancer

Abstract: Our study investigated the relationship between CT signs of colon cancer and the expression of miR-146a, to evaluate their predictive value in early diagnosis and of colon cancer. A total of 216 patients with colon cancer who were admitted to the Department of Hematology and Oncology in Yingcheng Hospital, the Second Hospital of Shandong University in Zhaoyuan City from January 2013 to March 2017 were selected as the study group. At the same time, 150 patients with benign colitis were also included to serve as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…We observed that the most statistically significant miRNA downregulated in the TME cells, miR-146a, was a geromiR ( Figure 5 A). Liu et al [ 22 ] found that the relative expression level of miR-146a in the peripheral blood of colon cancer patients was significantly lower than that of a control group with benign colitis. Simanovich et al [ 23 ] showed that miR-146a-5p functions as a control switch between angiogenesis and cell death, its neutralization can manipulate the crosstalk between tumor cells and macrophages, and profoundly change the TME.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that the most statistically significant miRNA downregulated in the TME cells, miR-146a, was a geromiR ( Figure 5 A). Liu et al [ 22 ] found that the relative expression level of miR-146a in the peripheral blood of colon cancer patients was significantly lower than that of a control group with benign colitis. Simanovich et al [ 23 ] showed that miR-146a-5p functions as a control switch between angiogenesis and cell death, its neutralization can manipulate the crosstalk between tumor cells and macrophages, and profoundly change the TME.…”
Section: Resultsmentioning
confidence: 99%
“…In CRC patients, miR-146a expression level decreased in progressed tumors [ 9 ]. Since miR-146a plays important roles in the development of CRC, we presumed that miR-146a rs2910164 variants could influence the susceptibility to CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Adami et al indicated that miR-146a was overexpressed in primary gastric tumor tissues without the status of chronic Helicobacter pylori infection and expressed a related lower level in progressed gastric cancer [ 8 ]. In addition, a recent study reported that miR-146a expression level decreased in progressed CRC patients with lymph node metastasis [ 9 ]. Thus, miR-146a was considered to be implicated in the development and progression of cancer [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies have shown the value of serum markers combined with CT diagnosis. The studies by Liu et al [30] showed that miR-146a combined with CT can significantly improve the diagnostic efficiency of colon cancer, and can provide a great prediction value for invasion and metastasis of colon cancer. He et al [31] and others have proposed that the use of miRNA can improve CT diagnosis of lung cancer and pulmonary nodules and greatly reduce false positives diagnosis.…”
Section: Discussionmentioning
confidence: 99%